Traditional Market Development Strategy in Kudus, Central Java According to Islamic Economic Perspective - Nelly Shofia; Indra, Indra (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Traditional markets are one of the cornerstones of life for people, especially small traders. However, the existence of traditional markets is currently decreasing due to several reasons, including the location of traditional markets close to modern markets, lack of infrastructure, safety and comfort of traditional markets, and so on. So this makes people slowly leave traditional markets and switch to modern markets. The aim of this study is to formulate strategies that are relevant to traditional market conditions in Kudus, Central Java and in accordance with sharia principles. The research method used is Analytic Network Processes (ANP). This study used 7 informants from academics, practitioners and regulators. The results of this study are that traditional market development strategies in the form of revitalization, infrastructure development and traditional market quality rank first as the most relevant strategies to use. This was followed by the next strategy, namely Locations that Support the Public Interest, followed by Increasing Trader Capacity and Skills, then Sharia-Based Government Policy and Improving the quality and Diversification of Halal and Tayyib Products.